Environmental factors affecting the distribution of African elephants in the Kasigau wildlife corridor, SE Kenya. (12th August 2017) - Williams, Harry F.; Bartholomew, David C.; Amakobe, Bernard; Githiru, Mwangi
Abstract: The African elephant, Loxodonta africana, is under threat from habitat loss, poaching and human–elephant conflict. To mitigate for impact of habitat loss and reduce conflict, connectivity between elephant habitats can be improved through the protection of corridor areas. This study looks at elephant distribution and movement patterns within the Kasigau Wildlife Corridor (KWC) within the Tsavo Conservation Area in South‐east Kenya. Elephant presence data were obtained from observations by rangers during routine patrols across KWC, and were analysed in MaxEnt. The environmental factors predicting elephant distribution and density were tested, as well as the relationship between elephant maximum entropy and the presence and abundance of other wildlife. Seasonal variations in temperature and precipitation, plus presence of waterholes were found to play significant roles in elephant distribution across KWC. Higher elephant densities were not found to correlate with lower densities of other wildlife species; indeed, during the dry seasons, elephant presence was associated with greater wild herbivore densities. Besides illustrating the importance of the KWC for elephant conservation in the Tsavo ecosystem, both as a key corridor and habitat, this study also hopes to highlight the untapped utility of routine ranger patrol data, and encourage the use of such presence‐only data for deducing important knowledge for conservation of biodiversity.